Embryogenic cultures and somatic embryos development from mature seeds of jabuticaba (Plinia cauliflora (Mart.) Kausel) - OLIVEIRA,FABRÍCIA LORRANE R. (2022)
Abstract Plinia cauliflora is an important Brazilian species that produces highly appreciated fruits, with a great potential of commercialization. However, the high cost of seedlings is a bottleneck for the expansion of commercial orchards. The present study aimed to investigate somatic embryogenesis as a propagation method for P. cauliflora using seeds as explants. To induce embryogenic mass (EM) and somatic embryo (SE) development we evaluated the supplementation of culture medium with different concentrations of 2,4-dichlorophenoxyacetic acid (2,4-D), combined or not with activated charcoal (AC). For the embryo maturation, we investigated the effects of AC, polyethylene glycol (PEG), Gelzan®, 6-benzylaminopurine and gibberellin supplementation. For the EM induction, the best results were obtained in MS culture medium supplemented with 300 μM 2,4-D and 1 g L-1 AC. During the first maturation phase, the supplementation of 30 g L-1 PEG improved the somatic embryo formation at the torpedo and cotyledonary stages, whereas the maturation treatments did not result in the conversion of the embryos into plantlets. The anatomical analysis showed that the 2,4-D presence for 60 days may have been deleterious for embryonic development. These results represent the first report of P. cauliflora somatic embryogenesis and its feasibility for mass propagation.